Photoluminescence Emission and Structure Study in ZnO:Ag nanorods - Erick Velázquez Lozada; G M Camacho-González; J M Quino-Cerdan (Department of Physics, Sebelas Maret University, 2015)
Scanning electronic microscopy (SEM) andX ray diffraction (XRD) have been applied to the study of structural and optical properties of ZnOnanocrystals prepared by the ultrasonic spray pyrolysis (USP) at different temperatures. The variation of temperatures and times at the growth of ZnO films permits modifying the ZnO phase from the amorphous to crystalline, to change the size of ZnOnanocrystals (NCs), as well as to vary their photoluminescence spectra.